2020
DOI: 10.12688/f1000research.19056.4
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial manifestations of mucocutaneous leishmaniasis: a case series from Brazil

Abstract: Dentists play a fundamental role in the early diagnosis of oral leishmaniasis. Although these lesions are rare at oral mucosa, this is one of the manifestations sites of the disease This study reports seven clinical cases of orofacial mucocutaneous leishmaniasis. All had leishmaniasis diagnosis confirmed by laboratory tests, with orofacial involvement. Five out of the seven cases were males, and in four cases, patients had associated comorbidities. Late diagnosis was observed, resulting in treatment delay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Only one patient tested positive for HIV and only two were women [6]. Falcão et al [7] reported seven new cases involving the oral cavity in Brazil. Of these cases, ve were men, one was HIV-positive, and most had ulcerated lesions on the lips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one patient tested positive for HIV and only two were women [6]. Falcão et al [7] reported seven new cases involving the oral cavity in Brazil. Of these cases, ve were men, one was HIV-positive, and most had ulcerated lesions on the lips.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the New World, oral leishmaniasis is considered a mucocutaneous manifestation of tegumentary leishmaniasis, and is not typically recognized as the primary site of infection. However, cases of mucosal leishmaniasis with primary oral involvement, including isolated lesions on the oral mucosa, have been reported [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…After the removal of duplicates, 4377 reports were retrieved through the searches in different databases. Of these, 10 were included that reported on a total of 192 ML patients [5,6,16,[34][35][36][37][38][39][40]. 160 full texts were excluded because they reported on less than five ML patients and seven because they presented no data at the individual patient level.…”
Section: Study Selection and Data Obtainedmentioning
confidence: 99%
“…Respiratory tract invasion and secondary bacterial infection might lead to patient's demise. Being a potentially life-threatening disease, it requires immediate and early diagnosis, treatment and sometimes seen in immunocompromised individuals (Falcao et al, 2020). It is usually found in Latin America, caused by Leishmania braziliensis, Leishmania panamensis and Leishmania guyanensis (Sachdeva and Sharma, 2016).…”
Section: Mucocutaneous Leishmaniasismentioning
confidence: 99%